Trypsin and chymotrypsin proteinase inhibitors of arid legumes - BABU, S RAMESH; SUBRAHMANYAM, B (The Indian Journal of Agricultural Sciences, 2014)
Trypsin and chymotrypsin inhibitor activities were studied using cowpea, cluster bean, babul and algaroba seeds. Results of this study indicated that the mean value obtained for all the accessions examined was 52.84±3.05 TIU/mg in Acacia senegal which was significantly higher than that found for the other arid legumes studied. The majority of the cowpea accessions examined fell within the range of 15-45 TIU/mg and the significantly highest trypsin inhibitory activity (8.03±0.55 TIU/mg) was found in accession, IC-311403. In Acacia senegal, the trypsin inhibitors content ranged from 34.77±0.09 in IC-330522 to 85.45±7.02 TIU/mg in local cultivar. Algaroba and cluster bean have not shown any chymotrypsin inhibitory activity. Significant variability for chymotrypsin inhibitor content was observed among the various accessions of cowpea and A. senegal species. The accessions of arid legumes including tree legumes were found to be better and hence could be explored for further development and selection of good sources of PIs for insect resistance in transgenic crops.